2008
DOI: 10.1021/es071566r
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Scale Comparison of Enhanced Coagulation with Magnetic Resin Plus Coagulation Systems

Abstract: Previous work has shown that magnetic ion-exchange treatment before coagulation gives high natural organic matter (NOM) removal and reduced levels of disinfection byproduct when compared to conventional enhanced coagulation. The impact of the resin process on the downstream floc formation process after coagulation and the subsequent effect on clarification has not previously been shown. Water containing high concentrations of NOM were treated at pilot scale using (1) conventional enhanced coagulation and compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(20 citation statements)
references
References 34 publications
(55 reference statements)
1
17
0
1
Order By: Relevance
“…Subsequently, clarification followed by SIX was found to yield very low residual organics concentrations (Fig. 3d), in keeping with previously reported findings (Fearing et al 2004;Jarvis et al 2008;Humbert et al 2007;Fan et al 2008;Singer and Bilyk, 2002).…”
Section: Scoping Studies Six Clarification or Clarification + Six (supporting
confidence: 91%
“…Subsequently, clarification followed by SIX was found to yield very low residual organics concentrations (Fig. 3d), in keeping with previously reported findings (Fearing et al 2004;Jarvis et al 2008;Humbert et al 2007;Fan et al 2008;Singer and Bilyk, 2002).…”
Section: Scoping Studies Six Clarification or Clarification + Six (supporting
confidence: 91%
“…Hussain et al indicated that zirconium tetrachloride was more effective for the removal of low-medium molecular weight organics, which could limit the formation of disinfection byproducts (DBPs) oen known to be carcinogenic. 12,13 Besides, Zr salt was also conrmed to be effective for arsenic removal, 14 and in the treatment of paper and pulp wastewater. 15 What also worth to be noticed is organic membrane fouling, since it hinders the widespread application of membrane techniques during surface water treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Anion exchange resin (AER) is an important adsorbent in water purification to remove anionic pollutants (Bolto et al, 2002;Boyer et al, 2008;Higgins, 1973;Huang et al, 2012;Jarvis et al, 2008). However, the application of AERs has been limited for many years because of capacity loss after regeneration and the increasing volume of desorption concentrate, both of which are attributed to the resin fouling (Abrams, 1982).…”
Section: Introductionmentioning
confidence: 99%